An assessment of the awareness and practices regarding HIV/AIDS among married women of the reproductive age group in urban slums of Eastern Uttar Pradesh - Khan, Huma; Mishra, Saurabh; Srivastava, Dhirendra Kumar; Srivastava, Reena (International Journal Of Community Medicine And Public Health, 2019)
Background: HIV/AIDS is such a dreaded disease which can be prevented if the people are aware of the ways to do so. Urban slums share a specific position in the demographic profile of district because of the inequalities of health care system where the rural health care system is far to reach and the more flourished private health care system is unaffordable for most of the inhabitants. HIV/AIDS is not only a health-related problem but it also has socioeconomic, behavioral and cultural aspects. Methods: Descriptive cross-sectional among currently married women in reproductive age group (15-49 years) residing in any of the selected urban slums of district Gorakhpur. Cluster sampling was used and clusters were chosen by probability proportional to size (PPS) method of cluster sampling from a list of urban slums obtained from District Urban Development Authority (DUDA), Gorakhpur. The final sample size was 600. Results: 82% of women had ever heard about HIV/AIDS and 72% of women got the knowledge about HIV through television followed by 56% of woman who got knowledge by relatives and friends. 68% of woman believes that the mode of transmission of HIV is unsafe sex followed by 58% of women who believed that infected blood transfusion is the mode of transmission of HIV. Conclusions: Awareness is crucial in the prevention and control of HIV/AIDS. Women should have more access to the knowledge resources and facilities for testing and prevention of HIV/AIDS.